2018
DOI: 10.3748/wjg.v24.i20.2137
|View full text |Cite
|
Sign up to set email alerts
|

Immune therapies in pancreatic ductal adenocarcinoma: Where are we now?

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers, mostly due to its resistance to treatment. Of these, checkpoint inhibitors (CPI) are inefficient when used as monotherapy, except in the case of a rare subset of tumors harboring microsatellite instability (< 2%). This inefficacy mainly resides in the low immunogenicity and non-inflamed phenotype of PDAC. The abundant stroma generates a hypoxic microenvironment and drives the recruitment of immunosuppressive cells through cancer-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 131 publications
(122 reference statements)
2
82
0
Order By: Relevance
“…Multiple hypotheses may explain why pancreatic cancer has not responded well to various immunotherapy treatments (20-23). One major hypothesis relates to the dense stroma within the TME (24). Preclinical observations have suggested that because of the presence of a complex desmoplastic stroma, immune cells-particularly T cellscannot infiltrate the TME (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple hypotheses may explain why pancreatic cancer has not responded well to various immunotherapy treatments (20-23). One major hypothesis relates to the dense stroma within the TME (24). Preclinical observations have suggested that because of the presence of a complex desmoplastic stroma, immune cells-particularly T cellscannot infiltrate the TME (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the activity of programmed cell death 1 receptor (PD-1)/programmed cell death ligand 1 (PD-L1)-and cytotoxic T-lymphocyte-associated protein 4 (CTLA4)-blocking agents against PDAC is limited and the activity of novel combinations of immunotherapeutic agents reported so far has been at best disappointingly low in patients with microsatellite stable PDAC. 55,56 The outcome of autophagy modulation to treat cancer is the result of a complex combination of the effect of autophagy on tumour cells and cells of the microenvironment, which includes immune cells. In addition, the interaction of various cell populations such as macrophages and fibroblasts, which both play a critical role in the immune context of PDAC, and T cells, renders deciphering the exact role of autophagy even more challenging.…”
Section: Autophagy and The Anti-tumour Immune Responsementioning
confidence: 99%
“…For esophageal cancer, several clinical trials, which evaluate the combination of chemoradiotherapy with ICIs as neoadjuvant or first-line treatment are now ongoing ( Table 2). ICI monotherapy activity was not observed in advanced pancreatic cancer patients due to the low immunogenicity and lymphocyte infiltration of tumor lesions [87]. To reverse the immunosuppression of pancreatic cancer, the combination of ICIs with cytotoxic agents, including gemcitabine, irinotecan, 5-FU, and albumin-bound paclitaxel is being evaluated by clinical trials.…”
Section: Combination With Chemotherapy or Radiotherapymentioning
confidence: 99%